WHO Expert Committee on Specifications for Pharmaceutical Preparations thirty-ninth report. (Technical report series (World Health Organization) ;, 2005)
This report discusses the monographs on antiretrovirals proposed for inclusion in The International Pharmacopoeia and specifications for radiopharmaceuticals, quality specifications for antituberculosis drugs and the revision of the monograph on artemisinin derivatives, as well as quality control of reference materials, good manufacturing practices, inspection, distribution and trade, and other aspects of quality assurance of pharmaceuticals, and regulatory issues. Several annexes include an amendment to good manufacturing practices: main principles regarding the requirement for the sampling of starting materials, guidelines on good manufacturing practices regarding water for pharmaceutical use, guidelines on the sampling of pharmaceutical products, and draft guidelines for registration of fixed-dose combination medicinal products.